Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/eye.2016.232
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of indocyanine green angiography and optical coherence tomographic angiography in polypoidal choroidal vasculopathy

Abstract: PurposeTo compare optical coherence tomographic angiography (OCTA) and indocyanine green angiography (ICGA) images for detecting polypoidal lesions (PLs) and branching vascular networks (BVNs), and to measure the polypoidal areas (PAs) in patients with polypoidal choroidal vasculopathy (PCV).MethodsAll patients underwent ICGA, optical coherence tomography (OCT), and OCTA. We compared the detection sensitivity for PL and BVN, as evaluated by the ICGA and OCTA images. Furthermore, PA measured by ICGA was divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 23 publications
7
42
0
Order By: Relevance
“…3 and 4). This finding confirms previous studies in eyes with PCV and type 1 nAMD, where lesion sizes were statistically significantly smaller in OCTA than in ICGA 26,27 without the systematic approach used in our study differentiating between lesion types.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…3 and 4). This finding confirms previous studies in eyes with PCV and type 1 nAMD, where lesion sizes were statistically significantly smaller in OCTA than in ICGA 26,27 without the systematic approach used in our study differentiating between lesion types.…”
Section: Discussionsupporting
confidence: 82%
“…A higher sampling density in a smaller volume (3 3 3 mm) could potentially increase CNV detection. Yet, previous studies 26,27 showed the same results, namely larger CNV-A in FA and ICGA compared with OCTA.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…On the other hand, in the study using 3-dimensional OCT, Hisatomi et al [35] discussed the possibility that the temporal macular thinning would in some cases be due to the damage of the retinal nerve fiber layer by incision and grasping during ILM peeling in eyes with retinal detachment. Recently, many physicians have been focusing on the diagnostic potential of OCT angiography, a state-ofthe-art technique that can provide noninvasive imaging of the retinal vascular network [36,37] . There is a possibility that we will obtain many new findings with regard to the effects of ILM peeling and SO endotamponade on retinal thinning by analysis using OCT angiography.…”
Section: Discussionmentioning
confidence: 99%
“…A few small case series have shown that OCTA can demonstrate the BVN in most cases but has difficulty showing polyps as they may appear as hypoflow lesions [25][26][27][28]. Two slightly larger case studies in Japan noted that OCTA is able to detect the BVN and polyps in about 75-85% of eyes [29,30]. However, these prior studies were limited by small sample sizes of 21 eyes or fewer.…”
Section: Introductionmentioning
confidence: 96%